ANALISIS KINERJA BELANJA DAERAH DI KABUPATEN SAROLANGUN - Irhamna Andriani (Jurnal Manajemen Terapan dan Keuangan, 2020)
The purpose of this study is to analyze the development of regional spending in Sarolangun Regency and to analyze how the performance of regional spending in Sarolangun Regency. The method used is descriptive and quantitative analysis using regional expenditure development analysis, expenditure growth analysis, spending harmony analysis, spending efficiency analysis. The results showed that the development of regional spending in Sarolangun Regency during 2006 - 2012 experienced an average development of 20.67%. In terms of harmony, regional expenditure performance is said to be good in allocating regional expenditure because the allocation of operational expenditure is greater than capital expenditure. Meanwhile, the average level of government spending efficiency in Sarolangun Regency during 2006 - 2012 was 86.64% which is classified as efficient